Dietary polyethylene inclusion affecting rabbit's performance - Abdelhamid M. Abdelhamid; Ahmed A. M. Abdel Hamid; Mahmoud A. E. Hassan; Manar A. Almnsy; Adel E. M. Ibrahim (Journal of Applied Science, Engineering, Technology, and Education, 2021)
A feeding experiment was conducted with rabbits as experimental animals for 2 months at 4 treatment groups under the same environmental conditions. The aim was to study the toxic effects of dietary graded levels of polyethylene (PE, 0, 1, 2, and 4 g/ton diet). The main effects were that some animals fed the PE-contaminated diets suffered from mange, diarrhea, weakness, and/or loss of weight. Post-mortem examination of the contaminated-diets fed rabbit revealed presence of bad smell liquids in its abdomen, residues of collective PE in the small intestine, collective feces in one part of the intestine and the parts were filled with aqueous accumulation, the color of one hepatic lobule was pale, and the lungs' color was bloody red. Yet, feed intake and water consumption increased by feeding the contaminated diets. Moreover, animals offered the contaminated diets reflected heavier body weight. However, the feed conversion (utilization) was negatively affected by the PE- contaminated diet; since, dietary PE-inclusion increased apparently feed consumption than the real body weight gain. Slaughter test of the PE-treated animals reflected many remarks including loss of rabbit's weight; increased skin weight, skin was thick and dough, changes in the color and quality of the carcass flesh, easy broken bone. When these animals were eviscerated, it were observed white-colored lungs, with necrosis and bloody infiltration, small-sized liver, with blackly-red color, enlarged gall bladder, narrow diameter of the small intestine, presence of collective mass of PE on the internal wall of the small intestine. The presence of PE in the experimental diets was responsible for significant lowering the specific gravity of the treated animals' bone, as well as their flesh moisture and fat; yet, their crude protein increased besides their edible parts and boneless meat percentages increased too, but not significantly. Dietary contamination with PE reflected its residues in the rabbits' flesh and increased the flesh content of ash (P>0.05). The contaminated diets were responsible for significantly (P≤0.05) evaluating lymphocytes %, MCV, MCH, and PLT and lowering both monocytes and granulocytes % as well as RBCs count. Significant (P≤0.05) increases in albumin, creatinine and uric acid concentrations and decreases of ALT activity were recorded with feeding rabbits the PE-contaminated diets; but, Cho. and Trig. concentrations were decreased (P≤0.05). There was a significant increase of scores of hepatic congestion and necrosis in liver from rabbits group received 0.4 PE when compared with control group. Statistical analysis shows significant increase of scores of renal congestion, fibrosis and acute tubular necrosis in group received 0.4 PE when compared with control group. Hence PE negatively affected rabbits' performance, health and quality, and may affect the consumers' health too.